2013
DOI: 10.1073/pnas.1217505110
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan of neurons is uncoupled from organismal lifespan

Abstract: Neurons in mammals do not undergo replicative aging, and, in absence of pathologic conditions, their lifespan is limited only by the maximum lifespan of the organism. Whether neuronal lifespan is determined by the strain-specific lifetime or can be extended beyond this limit is unknown. Here, we transplanted embryonic mouse cerebellar precursors into the developing brain of the longer-living Wistar rats. The donor cells integrated into the rat cerebellum developing into mature neurons while retaining mouse-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
0
46
0
2
Order By: Relevance
“…It was also shown that the lifespan of neurons can be independent of the survival of the host. In the absence of pathological conditions, the survival on mammalian neurons is only limited by the maximum lifespan of the organism, but when these neurones are transplanted in younger organisms, their survival continues in the longer living host . This may suggest that noemes could also experience increased survival which will be only limited by the survival of their host (i.e., the GB).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the lifespan of neurons can be independent of the survival of the host. In the absence of pathological conditions, the survival on mammalian neurons is only limited by the maximum lifespan of the organism, but when these neurones are transplanted in younger organisms, their survival continues in the longer living host . This may suggest that noemes could also experience increased survival which will be only limited by the survival of their host (i.e., the GB).…”
Section: Discussionmentioning
confidence: 99%
“…Postmitotic cells such as neurons can survive and function normally for the entire life of the animal, in some cases (e.g., fish, tortoises, whales) for over 200 years. Interestingly, the cellular niche can control the lifespan of these neurons; for example, embryonic neuron precursors from short-lived mice (~18 month life span) that are transplanted into rats (~30 month life span) live twice as long (Magrassi et al, 2013). The neurons arising from the transplanted neuronal precursors(Purkinje cells) remain smaller than the corresponding rat neurons but retain normal polarity and orientation with age; they also show a similar age-dependent loss of dendritic spines with age as seen in the rat neurons.…”
Section: Aging In Individual Cells – General Considerationsmentioning
confidence: 99%
“…For example, some types of mammalian neurons can remain perfectly alive without any need of replication throughout the lifespan of an organism and far beyond (Magrassi et al 2013). This means that in these dwelling neurons, over time no single molecule or even an atom is the same any more, whereas their organization is fully preserved.…”
Section: The Replicator Hypothesis and Errors Of Logical Typingmentioning
confidence: 99%